Regulation of myeloid and lymphoid cell development by O-glycans on Notch - Stanley, Pamela; Tanwar, Ankit (Frontiers in Molecular Biosciences, 2022)
Notch signaling via NOTCH1 stimulated by Delta-like ligand 4 (DLL4) is required for the development of T cells in thymus, and NOTCH2 stimulated by Notch ligand DLL1 is required for the development of marginal zone (MZ) B cells in spleen. Notch signaling also regulates myeloid cell production in bone marrow and is an essential contributor to the generation of early hematopoietic stem cells (HSC). The differentiation program in each of these cellular contexts is optimized by the regulation of Notch signaling strength by O-glycans attached to epidermal growth factor-like (EGF) repeats in the extracellular domain of Notch receptors. There are three major types of O-glycan on NOTCH1 and NOTCH2 - O-fucose, O-glucose and O-GlcNAc. The initiating sugar of each O-glycan is added in the endoplasmic reticulum (ER) by glycosyltransferases POFUT1 (fucose), POGLUT1/2/3 (glucose) or EOGT (GlcNAc), respectively. Additional sugars are added in the Golgi compartment during passage through the secretory pathway to the plasma membrane. Of particular significance for Notch signaling is the addition of GlcNAc to O-fucose on an EGF repeat by the Fringe GlcNAc-transferases LFNG, MFNG or RFNG. Canonical Notch ligands (DLL1, DLL4, JAG1, JAG2) expressed in stromal cells bind to the extracellular domain of Notch receptors expressed in hematopoietic stem cells and myeloid and lymphoid progenitors to activate Notch signaling. Ligand-receptor binding is differentially regulated by the O-glycans on Notch. This review will summarize our understanding of the regulation of Notch signaling in myeloid and lymphoid cell development by specific O-glycans in mice with dysregulated expression of a particular glycosyltransferase and discuss how this may impact immune system development and malignancy in general, and in individuals with a congenital defect in the synthesis of the O-glycans attached to EGF repeats.